Setting new horizons for OCBC through Small and Medium Enterprises. - Cheah, Zhuo Yue. (2008)
As Singapore aspires to be the next financial hub in Asia, there will be a constant influx of new and foreign financial institutions into our nation. As such, the local banks in Singapore will face unprecedented challenges and competition. We selected OCBC as the bank of our research with the intentions of creating multiple “blue ocean” strategies to help OCBC become the top Small and Medium Enterprises (SMEs) banking partner in South East Asia region.